2018
DOI: 10.1371/journal.pone.0208425
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies addressing the longevity of Bacillus subtilis spores – The first data from a 500-year experiment

Abstract: The ability to form endospores allows certain Gram-positive bacteria (e.g. Bacillus subtilis) to challenge the limits of microbial resistance and survival. Thus, B. subtilis is able to tolerate many environmental extremes by transitioning into a dormant state as spores, allowing survival under otherwise unfavorable conditions. Despite thorough study of spore resistance to external stresses, precisely how long B. subtilis spores can lie dormant while remaining viable, a period that potentially far exceeds the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 57 publications
3
38
0
Order By: Relevance
“…In field experiment percent disease incidence and percent survival rate of plants, second season trial showed good results compared to the first season. Many researchers confirmed that the antagonistic fungi Trichoderma and Bacillus could survive for many years in soil (Longa et al, 2009;Setlow, 2014;Ulrich et al, 2018). So, our experiment confirmed that the population of antagonists was already present in next growing season in the soil because the incidence was minimum while survival rate was increased during second growing season.…”
Section: Discussionsupporting
confidence: 79%
“…In field experiment percent disease incidence and percent survival rate of plants, second season trial showed good results compared to the first season. Many researchers confirmed that the antagonistic fungi Trichoderma and Bacillus could survive for many years in soil (Longa et al, 2009;Setlow, 2014;Ulrich et al, 2018). So, our experiment confirmed that the population of antagonists was already present in next growing season in the soil because the incidence was minimum while survival rate was increased during second growing season.…”
Section: Discussionsupporting
confidence: 79%
“…Given the known longevity of spores 61 , it is expected that they would be able to regerminate after indefinite storage under these conditions. Spores can survive under more extreme environmental stresses.…”
Section: Spore Survival In 3d Printed Materialsmentioning
confidence: 99%
“…Spores are dormant and resistant cell types that serve as adaptive forms by which the bacteria survive extreme environmental stresses [36]. Some of the adverse conditions that the bacteria commonly encounter include bacteriocidal agents such as lysozyme, heat and ultraviolet radiation [37]. A large number of spores of a particular species in a habitat is a strong indication of previous or continuing growth and metabolism in that niche.…”
Section: Assembly Of Spore Cortex and Coat Proteinsmentioning
confidence: 99%